2013
DOI: 10.1002/2013ja019266
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal variation in Global Navigation Satellite Systems TEC and topside ion density over South American sector associated with the four‐peaked wave structures

Abstract: [1] Recent observations of the low-latitude ionospheric electron density revealed a four-peaked longitudinal structure in the equatorial ionization anomaly when plotted at a constant-local-time frame. It was proposed that neutral wind-driven E region dynamo electric fields due to nonmigrating tidal modes are responsible for this pattern. We examine the four-peaked structure in the observed topside ion density and its manifestation as longitudinal structures in total electron content (TEC) over South America. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 66 publications
2
15
1
Order By: Relevance
“…When the DE3 E layer wind dynamo electric field is mapped to the F layer, it causes DE3 changes in the electron density through vertical transport processes. The annual and seasonal variations of DE3 are similar to those of ionospheric parameters, which support the E-F layer electric field coupling mechanism (Lin et al 2007;Kil et al 2008;Wan et al 2008;England et al 2009;Fang et al 2009;Oberheide et al 2009;Häusler and Lühr 2009;Mukhtarov and Pancheva 2011;Brahmanandam et al 2011;Wu et al 2012;Pedatella et al 2012;Nogueira et al 2013).…”
Section: Introductionsupporting
confidence: 66%
“…When the DE3 E layer wind dynamo electric field is mapped to the F layer, it causes DE3 changes in the electron density through vertical transport processes. The annual and seasonal variations of DE3 are similar to those of ionospheric parameters, which support the E-F layer electric field coupling mechanism (Lin et al 2007;Kil et al 2008;Wan et al 2008;England et al 2009;Fang et al 2009;Oberheide et al 2009;Häusler and Lühr 2009;Mukhtarov and Pancheva 2011;Brahmanandam et al 2011;Wu et al 2012;Pedatella et al 2012;Nogueira et al 2013).…”
Section: Introductionsupporting
confidence: 66%
“…Comparing the results obtained from our theoretical calculations and the observations, we may observe that the SUPIM results are underestimating the observational results. Some possible causes for the differences between the model results and observations can be the inefficiency of the input parameters for zonal electric field, thermospheric neutral winds [see Nogueira et al ., ], and the response of the neutral atmosphere densities to the solar flare [ Sutton et al ., ]. The most pronounced deficiency of the present modeling is in the EUV flux for wavelengths larger than 40 nm, for which we had no enough data from EVE satellite to incorporate in our simulations.…”
Section: Resultsmentioning
confidence: 99%
“…We have modeled the field line-integrated Cowling conductivity using the SUPIM-INPE Sellek, 1990, 1997;Souza et al, 2000Souza et al, , 2013Nogueira et al, 2013;Santos et al, 2016). The SUPIM-INPE solves the time-dependent equations of continuity, momentum and energy along magnetic field lines to obtain the electron and ion densities of the low-latitude ionosphere.…”
Section: Model Simulations By Supim-inpementioning
confidence: 99%
“…We seek an explanation for this delay by modeling the Cowling conductivity variations produced by the flare enhanced X-ray and EUV fluxes in the equatorial and low-latitude ionosphere close to midday. We used the Sheffield University Plasmasphere-Ionosphere Model at National Institute for Space Research (SUPIM-INPE; Bailey et al, 1978Bailey et al, , 1993Nogueira et al, 2013;Santos et al, 2016), which has been found to simulate realistically the equatorial-low-latitude ionosphere. The modeling results showed that the flare-induced temporal delays in the EEJ response (and in turn in its ground manifestation) cannot be attributed to a corresponding delay in the flare-induced enhanced Cowling conductivity development.…”
Section: Introductionmentioning
confidence: 99%